2016
DOI: 10.3892/mmr.2016.5107
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoside protects human primary melanocytes against H2O2-induced oxidative damage

Abstract: Cuscutae semen has been shown to have beneficial effects in the treatment of vitiligo, recorded in the Chinese Pharmacopoeia, whereas the effects of its constituent compounds remains to be elucidated. Using a tetrazolium bromide assay, the present study found that hyperoside (0.5–200 µg/ml) significantly increased the viability of human melanocytes in a time- and dose-dependent manner. The present study used a cell model of hydrogen peroxide (H2O2)-induced oxidative damage to examine the effect of hyperoside o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…[11][12][13][14] It is considered that with penetration of the proprietary HP40 solution into the SK lesion, HP may act not only through its direct oxidation of organic tissues, generation of reactive oxygen species, and local lipid peroxidation but also through generation of local concentrations of oxygen that are toxic to SK cells. [15][16][17][18] Recent ex vivo skin implant studies of neonatal foreskin suggest that HP40 leads to less cytotoxicity and greater melanocyte viability than with liquid nitrogen. 19 The number of treatment sessions for each lesion in these studies was limited by protocol design to 2, and the optimal number of treatment sessions to clear all lesions was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] It is considered that with penetration of the proprietary HP40 solution into the SK lesion, HP may act not only through its direct oxidation of organic tissues, generation of reactive oxygen species, and local lipid peroxidation but also through generation of local concentrations of oxygen that are toxic to SK cells. [15][16][17][18] Recent ex vivo skin implant studies of neonatal foreskin suggest that HP40 leads to less cytotoxicity and greater melanocyte viability than with liquid nitrogen. 19 The number of treatment sessions for each lesion in these studies was limited by protocol design to 2, and the optimal number of treatment sessions to clear all lesions was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [15] found that HYP is an effective compound to protect cells against oxidative stress via haem oxygenase-1 (HO-1) induction. Yang et al [16] revealed that HYP protected the human primary melanocytes against oxidative damage through phosphoinositide 3kinase/AKT signally pathways .…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the PI3K–Akt signalling pathway protects against oxidative stress‐induced cell death . Specifically, geniposide protects cells from H 2 O 2 ‐induced apoptosis by activating the PI3K–Akt signalling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, geniposide protects cells from H 2 O 2 ‐induced apoptosis by activating the PI3K–Akt signalling pathway . The Bcl‐2 and caspase families, which are crucial proteins involved in the apoptosis response induced by oxidative stress, are downstream molecules of the PI3K–Akt signalling pathway. Pre‐treatment of H 2 O 2 ‐induced melanocytes with geniposide increased expression of the anti‐apoptotic protein Bcl‐2 and decreased expression of Bax, a pro‐apoptotic protein belonging to the Bcl‐2 family.…”
Section: Discussionmentioning
confidence: 99%